Comparative Efficacy of Bisphosphonates to Prevent Fracture in Men with Osteoporosis: A Systematic Review with Network Meta-Analyses. Issue 1 (June 2016) - Zhou, Junwen; Wang, Tiansheng; Zhao, Xilan; Miller, Donald; Zhai, Suodi
Abstract Introduction Osteoporosis is an under-recognized problem threatening men. Bisphosphonates are the main treatment but their comparative efficacy is unclear for men with osteoporosis. Therefore, we performed this systematic review with network meta-analyses to summarize the evidence of comparative efficacy of bisphosphonates in men with osteoporosis. Methods We completed network meta-analyses with a frequentist model to compare the efficacy of different bisphosphonates. Randomized controlled trials investigating bisphosphonates used in men with osteoporosis were included. The primary outcome was the rate of patients with a new vertebral fracture. The secondary outcome was the rate of patients with a non-vertebral fracture, which was defined as any fractures reported other than vertebral fractures. Pairwise meta-analyses were performed to compare bisphosphonates with placebo. We included open-label studies in the analyses as a sensitivity analysis. Results Ten trials were included, using alendronate, ibandronate, risedronate, and zoledronic acid. No significant difference was found between any pairs of alendronate, ibandronate, risedronate, and zoledronic acid for both vertebral and non-vertebral fractures. Zoledronic acid ranked as the most effective in preventing vertebral fracture in primary osteoporosis. Risedronate ranked best in preventing non-vertebral fracture in both primary osteoporosis and corticosteroid-induced osteoporosis. In the sensitivity analyses with the open-label studies, the ranking order did not change. Conclusion The current evidence for bisphosphonates used in men with osteoporosis is inadequate. On the basis of the current evidence, zoledronic acid is most effective at preventing vertebral fractures, while risedronate has the highest possibility to rank the first in preventing non-vertebral fracture in men with primary osteoporosis and corticosteroid-induced osteoporosis. More well-designed studies are needed to test our findings and to better know the comparative efficacy of bisphosphonate to prevent vertebral fracture in men with osteoporosis.